CMT Welding of Low Carbon Steel Thin Sheets - Stanciu, Elena Manuela; Pascu, Alexandru; Gheorghiu, Iulian (IOP Publishing, 2017)
This paper addresses to the cold metal transfer MAG welding of low carbon steel thin sheets. The paper highlights the advantages of using CMT process for but joining of S235 carbon sheets by comparing the CMT with the conventional synergic pulse MAG welding. A lower weld bead area and heat affected zone is obtained by the continuous movement of the wire, digitally synchronised with the short-circuit of the arc. CMT welding can produce good welds even in unfavorable conditions, such as using thin plates and high diameter wire.
Keywords: welding; CMT